Potential of Kelakai Leaf Flour (Stenochlaena palutris (Burn.f) Bedd) Acid Pretreatment As An Alternatife to Prevent Stunting: Potential of Kelakai Leaf Flour (Stenochlaena palutris (Burn.f) Bedd) Acid Pretreatment As An Alternatife to Prevent Stunting - Ayutha Wijinindnyah; Jerry Selvia; Husnul Chotimah; Susan E Luman Gaol (Universitas Airlangga, 2022)
Background: Kelakai (Stenochlaena palutris (Burm.f) Bedd), is one of the local plants in Central Borneo. Nutrition in Kelakai has the potential to prevent stunting. The prevalence of stunting in Central Borneo province is 32,83%, and above by WHO (20%). Acid pretreatment is a method to speed drying time, maintain color and nutrient loss. Objectives: This study aims to determine acid pretreatment on drying time, proximate test and minerals. Methods: Kelakai were soaked in citric acid, commercial and natural tamarind 0,5% for 5 minutes. Dried using oven at 500C until the moisture content is ≤ 10% and analyze: proximate, and minerals. Results: Citric acid pretreatment can make drying time fastest which 6 hours. The highest proximate levels of calcium (0,6021%) and iron (0,0150%) were obtained in the pretreatment of natural tamarind. Conclusions: Citric acid is the fastest drying time, and the natural tamarind pretreatment is better to maintain nutritional.